The Role of Family Function and Triadic Interaction on Preterm Child Development-A Systematic Review - Johanna Larsson; Lisa Nyborg; Elia Psouni (MDPI AG, 2022)
Preterm infants are at high risk of developmental disability/delay and are more dependent on their caregiving environment for regulation due to their neurological immaturity. A premature birth is also a major stressor to the family system that constitutes the infant's caregiving environment. The following systematic review investigates whether families with preterm children differ from families with full-term children in their interactions, and what impact the quality of family interaction has on child development. Using the Cochrane model, we conducted a systematic review of quantitative studies published in psycINFO, socINDEX, and PubMed, concerning family quality in triadic interactions in families with premature infants and children, and at least one child development outcome variable. The quality of these studies was assessed using the Newcastle-Ottawa scale assessment form for cohort studies (NOS). Eleven studies were included in the review. Quality of family interactions is either equal to or poorer in families with preterm children, compared with families with full-term children. Importantly, the link between quality of family interactions and child development outcome is stronger in preterm children compared with full-term children, regarding both positive and negative influence. Our results highlight the importance of strengthening family interactions in order to promote development in preterm children. Notably, this review provides the first systematic overview of family function and the quality of triadic interactions in preterm families. The limited number of studies with a family-system focus makes it difficult for us to draw any definitive conclusions, while underscoring the need for more observational studies, particularly post-infancy, to be able to identify specific aspects of family interactions that may be critical for preterm child development.